Understanding filamentary growth and rupture by Ag ion migration through single-crystalline 2D layered CrPS4 - Lee, Mi Jung; Kim, Sung-Hoon; Lee, Sangik; Yoon, Chansoo; Min, Kyung-Ah; Choi, Hyunsoo; Hong, Suklyun; Lee, Sungmin; Park, Je-Geun; Ahn, Jae-Pyoung; Park, Bae Ho (NATURE RESEARCH, 2020)
Memristive electrochemical metallization (ECM) devices based on cation migration and electrochemical metallization in solid electrolytes are considered promising for neuromorphic computing systems. Two-dimensional (2D) layered materials are emerging as potential candidates for electrolytes in reliable ECM devices due to their two-dimensionally confined material properties. However, electrochemical metallization within a single-crystalline 2D layered material has not yet been verified. Here, we use transmission electron microscopy and energy-dispersive X-ray spectroscopy to investigate the resistive switching mechanism of an ECM device containing a single-crystalline 2D layered CrPS4 electrolyte. We observe the various conductive filament (CF) configurations induced by an applied voltage in an Ag/ CrPS4/Au device in the initial/low-resistance/high-resistance/breakdown states. These observations provide concrete experimental evidence that CFs consisting of Ag metal can be formed inside single-crystalline 2D layered CrPS4 and that their configuration can be changed by an applied voltage. Density functional theory calculations confirm that the sulfur vacancies in single-crystalline CrPS4 can facilitate Ag ion migration from the active electrode layer. The electrically induced changes in Ag CFs inside single-crystalline 2D layered CrPS4 raise the possibility of a reliable ECM device that exploits the properties of two-dimensionally confined materials.